2017
DOI: 10.4067/s0717-75182017000100011
|View full text |Cite
|
Sign up to set email alerts
|

El Impacto De La Educación Alimentaria Nutricional en El Embarazo: Una Revisión De Las Experiencias De Intervención.

Abstract: INTRODUCCIÓNEl embarazo es uno de los momentos de mayor vulnerabilidad nutricional en la vida de la mujer ya que las necesidades de energía y nutrientes se encuentran aumentadas en virtud del crecimiento fetal y de la síntesis de tejidos maternos como el aumento del tamaño uterino, la hipertrofia de las glándulas mamarias y la acumulación de las reservas grasas. El estado nutricional de la madre previo a la gestación y los hábitos alimentarios implementados durante el embarazo, son condicionantes de importanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
0
10
0
3
Order By: Relevance
“…Maternal food consumption during pregnancy is important since inadequate amounts of essential nutrients can adversely affect both mother and child. During pregnancy, the development of maternal tissues, fetal growth [ 3 , 4 ], and breast milk production [ 5 ] increase nutritional requirements [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal food consumption during pregnancy is important since inadequate amounts of essential nutrients can adversely affect both mother and child. During pregnancy, the development of maternal tissues, fetal growth [ 3 , 4 ], and breast milk production [ 5 ] increase nutritional requirements [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal nutrition during pregnancy and lactation is important since inadequate amounts of essential nutrients can adversely affect both mother and child [1,2,3,4]. During pregnancy, the development of maternal tissues, fetal growth [5,6], and breast milk production [7] increase nutritional requirements [8].…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate maternal nutrition, and especially a deficit of essential nutrients, is associated with negative health outcomes in both the mother and the child [3][4][5][6]. The key nutrients that are particularly important during pregnancy and lactation include iron, folates, calcium and vitamin D [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D plays an important role in bone metabolism through the regulation of calcium homeostasis. Vitamin D deficiency has been linked to an increased risk of preeclampsia, gestational diabetes mellitus, and other specific conditions of certain tissues in pregnant women [5,[12][13][14][15].Additionally, recent studies and meta-analyses have revealed other health repercussions including adverse anthropometric outcomes, preterm birth, small for gestational age and adverse neurodevelopmental outcomes in childhood [16][17][18].…”
Section: Introductionmentioning
confidence: 99%